Efektivitas Pembelajaran PJOK Berbasis Gamifikasi dalam Meningkatkan Partisipasi Siswa Sekolah Dasar - Siprianus Nong Charlon (Educational Journal, 2026)
This study aims to analyze the effectiveness of gamification-based Physical Education, Sports, and Health (PJOK) learning in improving elementary school students’ participation. The research employed a literature review method by examining various scientific articles, national and international journals, and relevant references related to the implementation of gamification in education. Data were collected through literature searches in several academic databases using keywords related to gamification, physical education, student participation, and elementary education. The selected literature was analyzed using content analysis techniques. The findings indicate that the application of gamification elements, such as points, badges, leaderboards, levels, challenges, and rewards, can significantly enhance student participation in physical education learning. Furthermore, gamification has been found to improve learning motivation, student engagement, physical activity levels, and the overall learning experience. The results suggest that gamification is an effective instructional strategy that aligns with the developmental characteristics of elementary school students, who naturally enjoy play-based activities. Therefore, gamification-based PJOK learning can serve as an innovative approach to improve learning quality and increase student participation in elementary schools.